Mechanisms linking variation in spring environmental conditions to changes in the phenology and abundance of Calanus marshallae and Eucalanus bungii. (December 2021) - Tommasi, Desiree; Hunt, Brian P.V.; Pakhomov, Evgeny A.
Highlights: A mechanistic population model assesses drivers of copepod biomass. With a delayed phytoplankton bloom, copepod biomass is lower and peaks later. Changes in copepod phenology are driven by shifts in maturation and egg production. A late phytoplankton bloom is also associated with higher copepod mortality. Abstract: The recruitment of many fish species is thought to be dependent on a match with the timing of spring phytoplankton biomass. This process is mediated by zooplankton dynamics. However, it remains unclear how phenological changes are coupled across trophic levels, and what mechanisms link variation in spring phytoplankton timing to changes in the phenology and abundance of important zooplankton prey species. Here, a stage structured population model was used to simulate the population dynamics of the copepods Calanus marshallae and Eucalanus bungii over the spring period. Simulations successfully reproduced the interannual and seasonal variability in the abundance of the two species in three different years of observations. Variation in mortality was the main driver of the observed interannual differences in the size of the new diapausing cohort. When the phytoplankton bloom was late more of C. marshallae reproductive effort was lost to mortality. E. bungii experienced lower recruitment when the bloom was late because of a reduction in the numbers of females and an increase in the mortality of copepodites with a later birth date. For both copepod species, high mortality was associated with low chlorophyll concentrations and high temperatures. The biomass of the diapausing cohort of both species was reduced during an El Niño year and when the spring phytoplankton bloom was delayed.